Consumer Generated Advertisements:The Ten Commandments - Kumar, Amarjeet; Uniyal, Shantanu (Indian Journal of Marketing, 2009)
In this era of global recession and financial crisis, big corporate houses are experimenting with a paradigm called consumer generated advertising (CGA). CGA is the most recent development in the field of advertisements, where consumers of a product or services are being purposely involved in the advertisement campaign. Consumers are invited through press, blogs, wikis, forums or electronic media to prepare ad campaigns or suggestions for the respective company. CGA reduces the cost of advertising and creates awareness among loyal customers as well. Here in this article the probable causes for the failure are being analyzed and probable counter methods are being formulated through commandments. Ten Commandments for preparing a CGA plan for any organization are being attempted in this research paper.